2003
DOI: 10.1080/10915810305101
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Tissue Distribution and Elimination of 4-[3H]-Epigallocatechin Gallate in Beagle Dogs

Abstract: Polyphenols found in tea are potent antioxidants and have inhibitory activity against tumorigenicity. The purpose of the described study was to assess the absorption, tissue distribution, and elimination of epigallocatechin gallate (EGCG), the principal catechin found in green tea, in a nonrodent species. 4-[(3)H]-EGCG was administered to beagle dogs by intravenous (IV) and oral routes. Following IV administration of 25 mg/kg, radioactivity in the bloodstream resided predominantly in the plasma. Distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…We also used HPLC assay to evaluate the EGCG concentration in grass carp blood and kidney. These data suggest that once‐daily dosing of 150 mg/kg was determined to be the rational choice for controlling GCRV infection in grass carp (Liu, Ge, Wang, Cui, & Han, ; Swezey et al., ; Unno & Takeo, ).…”
Section: Discussionmentioning
confidence: 99%
“…We also used HPLC assay to evaluate the EGCG concentration in grass carp blood and kidney. These data suggest that once‐daily dosing of 150 mg/kg was determined to be the rational choice for controlling GCRV infection in grass carp (Liu, Ge, Wang, Cui, & Han, ; Swezey et al., ; Unno & Takeo, ).…”
Section: Discussionmentioning
confidence: 99%
“…The toxicokinetics of radiolabelled EGCG (intravenous, single dose, 25 mg/kg; oral, single dose, 250 mg/kg) have been investigated in beagle dogs (Swezey et al, 2003). This study found that approximately 20% of orally administered EGCG is absorbed systemically in beagle dogs compared with 1.6% (Chen et al, 1997) to 14% (Zhu et al, 2000;Zhu et al, 2001) in rats.…”
Section: Animal Data and In Vitro Datamentioning
confidence: 92%
“…In addition, EGCG can inhibit biochemical markers of tumor initiation and promotion, and thus inhibit the development and growth of cancer. Although low systemic bioavailability is a major obstacle in EGCG administration as reported in animal models Kim et al, 2000;Swezey et al, 2003], the promising health benefits of EGCG have convinced researchers to conduct human intervention studies. Pharmacokinetic research in humans indicates that, after oral administration of EGCG, which has poor gastrointestinal absorption, serum levels of EGCG were found at sub-micromolar or nanomolar ranges Henning et al, 2005], whereas the physiologically relevant serum concentrations of EGCG were at micromolar levels (10-100 M) .…”
Section: (-)-Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 98%